Ten years of experience in pre-transplant patients from an advanced heart failure center - when is the best time to step in?. (2nd May 2022) - Martinho, A; Alves, T; Rodrigues, C; Girao, A; Pais, J; Fernandes, L; Franco, F; Costa, S; Lourenco, C; Prieto, D; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) profiles provide important prognostic information for patients with advanced heart failure (AHF) hospitalized for clinical worsening. Purpose: Assess the prognosis and fate of patients with Advanced HF (AHF), in INTERMACS I-IV, admitted to an Advanced Heart Failure Unit during 10-years. Methods: Retrospective, single-center study with AHF' patients admitted for acute HF during January 2010 and December 2020 in an Advanced Heart Failure Care Unit (AHFCU), who required inotropic therapy (INTERMACS I-IV) and were candidates for heart transplant (<65 years). We assessed the baseline characteristics at the time of admission and the long-term outcomes: death, alive with optimized medical therapy (OMT) and device or transplantation, according to INTERMACS profiles. Results: For 10 years, 175 patients who met the inclusion criteria were admitted to the AHFC, mostly men (66.2%) and ischemic (30%), with a mean age of 52±10 years. At admission the patients had a mean Left Ventricle Ejection Fraction (LVEF) of 27±10% and a median NT-proBNP of 7230 pg/ml (IQR 3801 to 19882). During the 10-years on focus, 42% patients were transplanted (n=73), 38% (n=66) remained alive with optimized MT and device and 20% (n= 36) died. In-hospital mortality was significant different between profiles (p=0.001), 55% in INTERMACS I patients, 25% in II, and 17% in III-IV. Most transplanted patients (63%) were in INTERMACS IV, 16.4% in III, 12.3% in II and only 11% (n=8) in INTERMACS I (p=0.043). Conclusion: Our results reinforce the importance of early action in these patients, using INTERMACS profile to prognostic stratification, who is important to identify the ideal time for referral to an appropriate centre, to properly convey expectations to patients and families, and to plan treatment and follow-up strategies (transplant, circulatory mechanical support, or palliative care).